De-escalation of asymptomatic testing and potential of future COVID-19 outbreaks in US nursing homes amidst rising community vaccination coverage: A modeling study. Issue 23 (20th May 2022) - Singh, Brajendra K.; Walker, Joseph; Paul, Prabasaj; Reddy, Sujan; Gowler, Camden D.; Jernigan, John; Slayton, Rachel B.
Abstract: As of 2 September 2021, United States nursing homes have reported >675, 000 COVID-19 cases and >134, 000 deaths according to the Centers for Medicare & Medicaid Services (CMS). More than 205, 000, 000 persons in the United States had received at least one dose of a COVID-19 vaccine (62% of total population) as of 2 September 2021. We investigate the role of vaccination in controlling future COVID-19 outbreaks. We developed a stochastic, compartmental model of SARS-CoV-2 transmission in a 100-bed nursing home with a staff of 99 healthcare personnel (HCP) in a community of 20, 000 people. We parameterized admission and discharge of residents in the model with CMS data, for a within-facility basic reproduction number ( R 0 ) of 3.5 and a community R 0 of 2.5. The model also included: importation of COVID-19 from the community, isolation of SARS-CoV-2 positive residents, facility-wide adherence to personal protective equipment (PPE) use by HCP, and testing. We systematically varied coverage of mRNA vaccine among residents, HCP, and the community. Simulations were run for 6 months after the second dose in the facility, with results summarized over 1, 000 simulations. Expected resident cases decreased as community vaccination increased, with large reductions at high HCP coverage. The probability of a COVID-19 outbreak was lower as well: at HCP vaccination coverage of 60%, probability of an outbreak was below 20% for community coverage of 50% or above. At high coverage, stopping asymptomatic screening and facility-wide testing yielded similar results. Results suggest that high coverage among HCP and in the community can prevent infections in residents. When vaccination is high in nursing homes, but not in their surrounding communities, asymptomatic and facility-wide testing remains necessary to prevent the spread of COVID-19. High adherence to PPE may increase the likelihood of containing future COVID-19 outbreaks if they occur.